Mitofusins and the mitochondrial permeability transition: the potential downside of mitochondrial fusion - Papanicolaou, Kyriakos N. (American Physiological Society, 2012)
Mitofusins (Mfn-1 and Mfn-2) are transmembrane proteins that bind and hydrolyze guanosine 5′-triphosphate to bring about the merging of adjacent mitochondrial membranes. This event is necessary for mitochondrial fusion, a biological process that is critical for organelle function. The broad effects of mitochondrial fusion on cell bioenergetics have been extensively studied, whereas the local effects of mitofusin activity on the structure and integrity of the fusing mitochondrial membranes have received relatively little attention. From the study of fusogenic proteins, theoretical models, and simulations, it has been noted that the fusion of biological membranes is associated with local perturbations on the integrity of the membrane that present in the form of lipidic holes which open on the opposing bilayers. These lipidic holes represent obligate intermediates that make the fusion process thermodynamically more favorable and at the same time induce leakage to the fusing membranes. In this perspectives article we present the relevant evidence selected from a spectrum of membrane fusion/leakage models and attempt to couple this information with observations conducted with cardiac myocytes or mitochondria deficient in Mfn-1 and Mfn-2. More specifically, we argue in favor of a situation whereby mitochondrial fusion in cardiac myocytes is coupled with outer mitochondrial membrane destabilization that is opportunistically employed during the process of mitochondrial permeability transition. We hope that these insights will initiate research on this new hypothesis of mitochondrial permeability transition regulation, a poorly understood mitochondrial function with significant consequences on myocyte survival.